2007
DOI: 10.3732/ajb.94.12.1963
|View full text |Cite
|
Sign up to set email alerts
|

Genomic relationships between the cultivated peanut (Arachis hypogaea, Leguminosae) and its close relatives revealed by double GISH

Abstract: Arachis hypogaea is a natural, well-established allotetraploid (AABB) with 2n = 40. However, researchers disagree on the diploid genome donor species and on whether peanut originated by a single or multiple events of polyploidization. Here we provide evidence on the genetic origin of peanut and on the involved wild relatives using double GISH (genomic in situ hybridization). Seven wild diploid species (2n = 20), harboring either the A or B genome, were tested. Of all genomic DNA probe combinations assayed, A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
206
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 205 publications
(226 citation statements)
references
References 44 publications
16
206
0
4
Order By: Relevance
“…4 and Supplementary Table 11). In accordance with cytogenetic observations 8,26 , A08 could be assigned as the characteristic small ' A chromosome' (cytogenetic chromosome A09; Supplementary Fig. 23).…”
Section: Analysis Of Chromosomal Structure and Syntenymentioning
confidence: 89%
See 1 more Smart Citation
“…4 and Supplementary Table 11). In accordance with cytogenetic observations 8,26 , A08 could be assigned as the characteristic small ' A chromosome' (cytogenetic chromosome A09; Supplementary Fig. 23).…”
Section: Analysis Of Chromosomal Structure and Syntenymentioning
confidence: 89%
“…13), makes the assembly of the peanut genome sequence very challenging. However, the A and B subgenomes appear to have undergone relatively few changes since polyploidization: genomic in situ hybridization (GISH), using genomic DNA from the diploid species as probes, clearly distinguishes A and B chromosomes and does not show large A-B mosaics 7,8 . Also, the genome size of A. hypogaea is close to the sum of those for A. duranensis and A. ipaensis (1.25 and 1.56 Gb, respectively 14 ), indicating that there has been no large change in genome size since polyploidy.…”
Section: Openmentioning
confidence: 99%
“…These taxa are more diverse in karyotype formula and in the presence and distribution of heterochromatin (Raina and Mukai, 1999;Seijo et al, 2004). Tetraploid species have an AABB genome constitution, and it has been demonstrated that they originated by hybridization of two wild diploid species, one with the A genome and the other with the B genome Gregory, 1976, 1979;Seijo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Domestication of this wild allotetraploid is hypothesized to have resulted in the present day cultivated peanut (Arachis hypogaea L.) (Seijo et al 2007). This cross was successfully re-created, and resulted in fertile tetraploid progeny (Fávero et al 2006).…”
mentioning
confidence: 99%